A system for electronic disease reporting and management. - Terry, T.J., Jr (IEEE Engineering in medicine and biology magazine)
The collection and reporting of communicable disease information has long been a problem for public health officials. In April 1998, the New Jersey Institute of Technology (NJIT), under contract to the New Jersey Department of Health and Senior Services (DHSS), began work on a "Electronic Laboratory Surveillance System" (ELS) to gather and report such data. The aim of ELS was to determine the extent/spread of problems and minimize consequences through rapid reporting and dissemination of critical information. ELS was completely redesigned to be more user friendly and incorporate new direct-access functions to enable better follow-up of communicable disease reports. This article looks at the evolution of the ELS from a limited system to one that can play a critical role in identifying and linking bioterrorism events